Adrenal function status in patients with Paracoccidioidomycosis after prolongued post-therapy follow-up (2010)
ABSTRACT : This study assessed adrenal function in patients with paracoccididioidomycosis who had been treated to determine a possible connection between high antibody titers and adrenal dysfunction attributable to persistence of the fungus in adrenal gland. Adrenal gland function was studied in 28 previously treated patients, 2 (7.1%) of whom were shown to have adrenal insufficiency and 7 (259%) who showed a below normal response to stimuli by adrenocortico- tropic hormone. Paracoccidioides brasiliensis was detected in the adrenal gland from one of the patients with adrenal insufficiency. Although the study failed to demonstrate a significant difference between high antibody titers and low cortisol levels, the proportion of adrenal insufficiency detected and the subnormal response to adrenocorticotropic hormone confirmed that adrenal damage is an important sequela of paracoccidioidomycosis. Studies with a larger number of patients should be conducted to confirm the hypothesis of persistence of P. brasiliensis in adrenal gland after therapy.